The Perils of Haemorrhoids Treatment - Elnaim, Abdel Latif K; M.P.K, Wong; I, Sagap (IIUM Medical Journal Malaysia, 2019)
Treating problematic haemorrhoids has taken a long turmoil route. Its peak incidence is among 45 to 65 years of age group. Typically, problematic haemorrhoids present in multi-symptoms forms like a prolapsed lump, painless bleeding, discomfort, soiling, or itchiness. Many theories were postulated in the pathophysiology of symptomatic haemorrhoids. The sliding and engorged of anal cushion with hypervascularity is the most popular. This is an updated review of published English-language literature regarding the treatment of haemorrhoids. The treatment includes medical therapy, office procedures, and surgical operations. Merits and demerits of the different modalities of treatment of haemorrhoids are presented. The best treatment options are difficult to ascertain. It should be tailored to individualize treatment according to their presentation and severity. Up till recently, the excisional haemorrhoidectomies are considered the standard procedure for haemorrhoid treatment. These techniques produce significant post-operative pain to the patient, which hinders them from normal daily activity. Recent advancement in surgical intervention has focused on minimising severity of pain and enhances recovery.